InSight - a touch of imagination - Loo, Dawn Shu Xian (2017)
Insight is a 3D platformer game where you play as Sam, a boy who uses his imagination to aid himself in retrieving his stolen belongings from bullies. This report gives the animation and design perspective of the production of our game.